Kepemimpinan Kepala Sekolah Dasar Unggul (Studi SItus Di SD Muhammadiyah PK Kecamatan Ampel Kabupaten Boyolali) - Kustiyah, Kustiyah; , Prof. Dr. Sutama, M.Pd; , Dr. Suyatmini, M.Si (2016)
The purpose of the studis to describe the principal's leadership in managing human resources, infrastructure and the finance in SD Muhammadiyah PK Ampel Sub District, Boyolali regency. Qualitative research with ethnographic design. SD Muhammadiyah PK study places the District Ampel, Boyolali regency. When the study from August to February. The research subjects principals, teachers, students, human resource management, infrastructure and finance. The technique of collecting data through observation, interviews and documentation. The validity of the data using triangulation. Technical analysis of the data with the data collection, data reduction, data presentation, and conclusion. Research results with improved management of teacher competence and professionalism. Management of students with quality learning. Management infrastructure refers to the national standard of education infrastructure. Financial management refers to RAPBS.